Secretion of endoplasmic reticulum protein VAPB/ALS8 requires topological inversion. - Kamemura, K.; Kozono, R.; Tando, M.; Okumura, M.; Koga, D.; Kusumi, S.; Tamai, K.; Okumura, A.; Sekine, S.; Kamiyama, D.; Chihara, T. (Nature communications, 2024)
VAMP-associated protein (VAP) is a type IV integral transmembrane protein at the endoplasmic reticulum (ER). Mutations in human VAPB/ALS8 are associated with amyotrophic lateral sclerosis (ALS). The N-terminal major sperm protein (MSP) domain of VAPB (Drosophila Vap33) is cleaved, secreted, and acts as a signaling ligand for several cell-surface receptors. Although extracellular functions of VAPB are beginning to be understood, it is unknown how the VAPB/Vap33 MSP domain facing the cytosol is secreted to the extracellular space. Here we show that Vap33 is transported to the plasma membrane, where the MSP domain is exposed extracellularly by topological inversion. The externalized MSP domain is cleaved by Matrix metalloproteinase 1/2 (Mmp1/2). Overexpression of Mmp1 restores decreased levels of extracellular MSP domain derived from ALS8-associated Vap33 mutants. We propose an unprecedented secretion mechanism for an ER-resident membrane protein, which may contribute to ALS8 pathogenesis.